Deviant Dynamics of Resting State Electroencephalogram Microstate in Patients With Subjective Tinnitus - Cai, Yuexin; Huang, Dong; Chen, Yanhong; Yang, Haidi; Wang, Chang-Dong; Zhao, Fei; Liu, Jiahao; Sun, Yingfeng; Chen, Guisheng; Chen, Xiaoting; Xiong, Hao; Zheng, Yiqing (Frontiers in Behavioral Neuroscience, 2018)
Given the importance of central reorganization and tinnitus, we undertook the current study to investigate changes to electroencephalogram (EEG) microstates and their association with the clinical symptoms in tinnitus. High-density (128 channel) EEG was used to explore changes in microstate features in 15 subjects with subjective tinnitus and 17 age-matched controls. Correlations between microstate parameters and subjective tinnitus symptoms were also analyzed. An increased presence of class A microstate and decreased presence of class D microstate were found in coverage and lifespan of microstate parameters in the tinnitus patients. Syntax analysis also demonstrated an aberrant pattern of activity, with reduced transitions from Class D to B in tinnitus patients. Moreover, a significant positive correlation of tinnitus loudness with increased lifespan of microstate class C was found. Significant differences in temporal characteristics and syntax of the EEG microstate classes were found at rest between tinnitus patients and the healthy subjects. Our study indicates that EEG microstates may provide a possible valuable method to study large-scale brain networks, which may in turn be beneficial to investigation of the neurophysiological mechanisms behind tinnitus.